Impacts of the Point System and Immigration Policy Levers on Skill Characteristics of Canadian Immigrants - Charles Beach; Alan G. Green; Christopher Worswick (Queen's University, Department of Economics, 2006)
This paper examines how changes in immigration policy levers actually affect the skill characteristics of immigrant arrivals using a unique Canadian immigrant landings database. We first review the Canadian experience with a point system as part of its immigrant policy. Section III of the paper describes some overall patterns of immigrant arrivals since 1980. Section IV identifies some relevant hypotheses on the possible effects on immigrant skill characteristics of the total immigration rate, the point system weights and immigrant class weights. The "skill" admissions examined are level of education, age, and fluency in either English or French. Regressions are then used to test the hypotheses from Canadian landings data. It is found that (i) the larger the inflow rate of immigrants the lower the average skill level of the arrivals; (ii) increasing the proportion of skill-evaluated immigrants raises average skill levels; (iii) increasing point system weights on a specific skill dimension indeed has the intended effect of raising average skill levels in this dimension among arriving principal applicants; and (iv) increasing the proportion of skill-evaluated immigrants appears to have the strongest effects among the immigration policy levers.
Keywords: J0; J6; 330; immigration policy; points system; Canadian immigration; Migrationspolitik; Einwanderungsrecht; Migranten; Qualifikation; Kanada